A GAB Aergic anxiolytic-like trait of thymoquinone, possibly via diazepam-co-agonistic pathway - Islam, Muhammad (International Journal of Medicine, 2017)
This study evaluated the possible anxiolytic potential of thymoquinone (TQ), a promising component of Nigella sativa oil in male Swiss mice under unstressed and stressed conditions. A short-term physical stress (STPS) was produced by using an electric shaker. A new apparatus named as ‘swing apparatus’ was selected to carry out this study. TQ was tested at doses of 5, 10 and 20 mg/kg. In order to understand possible action mechanism, a GABA receptor agonist and an antagonist were used in this study. As agonist diazepam (DZP), while antagonist flumazenil (FZL) was used at 2 and 2.5 mg/kg doses. Treatments were given intraperitoneally. The brain GABA levels were determined by UV-spectrophotometric method. The results suggest that, TQ dose-dependently exerted a significant (p<0.05) anxiolytic effect in rodents, which was confirmed by the calming effect of the experimental animals in comparison to the vehicles' NC, DZP and FZL groups. An augmentation of the movements of the animals was observed in STPS applied groups. GABA levels in the mouse brain were also found to link with the behavioral activity, where TQ co-treated with DZP augmented the calming effect by decreasing GABA levels, which was reversed by the FZL pre- and post-treated groups, demonstrating possible co-agonistic and antagonistic effects with DZP and FZL, respectively. Therefore, this study suggests an involvement of GABAergic, possibly DZP-co-agonistic anxiolytic-like effect of TQ.